The synergistic steric hindrance effect in the preparation of polyether ether ketone composites by powder slurry method. Issue 4 (15th February 2022) - Song, Jiupeng; Zhao, Yan; Xiong, Shu; Sun, Mingchen; Duan, Ziqi; Li, Shuang; Wang, Kai
Abstract: The preparation of continuous carbon fiber reinforced polyether ether ketone (PEEK) composites by the powder slurry method has many advantages, but the stability of PEEK suspension is required to be high. So far, there is a lack of in‐depth studies on the aqueous suspension of PEEK. In this study, two non‐ionic surfactants were selected for compounding. Then PEEK aqueous suspension and continuous carbon fiber reinforced PEEK composites were prepared. The stability mechanism of PEEK aqueous suspension with different surfactants was analyzed. Studies have shown that in the PEEK aqueous suspension, Triton X‐100 can help to infiltrate the PEEK powder. The steric hindrance of polyethylene glycol contributes to the stability of the suspension. The synergistic steric hindrance effect of the two surfactants can increase the stability time of PEEK suspension from 5 min to more than 50 min. The PEEK composites prepared by the powder slurry method has good quality stability, the fiber volume fraction is about 60%, the flexural strength of the composites can reach 1336 MPa, and the interlayer shear strength can reach 106 MPa. This study provides useful insights for the stability mechanism of PEEK aqueous suspension, and can guide the preparation process of thermoplastic composites by powder slurry method. Abstract :